Towards an effective poliovirus laboratory containment strategy in Nigeria (2018)
Background: The Global Commission for the Certification of the Eradication of Poliomyelitis will declare the world free of wild poliovirus transmission when no wild virus has been found in at least 3 consecutive years, and all laboratories possessing wild poliovirus materials have adopted appropriate measures of containment. Nigeria has made progress towards poliomyelitis eradication with the latest reported WPV type 1 on 21 Aug 2016 after 2 years without any case. This milestone achievement was followed by an inventory of biomedical laboratories completed in November 2015 with the destruction of all identified infectious materials. This paper seeks to describe the poliovirus laboratory containment process in Nigeria on which an effective containment system has been built to minimize the risk of virus re-introduction into the population from the laboratories. Methods: A national survey of all biomedical facilities, as well as an inventory of laboratories from various sectors, was conducted from June November 2015. National Task Force (NTF) members and staff working on polio administered an on-site questionnaire in each facility. Laboratory personnel were sensitized with all un-needed materials destroyed by autoclaving and incineration. All stakeholders were also sensitized to continue the destruction of such materials as a requirement for phase one activities. Results: A total of 20,638 biomedical facilities were surveyed with 9575 having laboratories. Thirty laboratories were found to contain poliovirus or potentially infectious materials. The 30 laboratories belonged to the ministries of health, education, defence and private organizations. Conclusions: This article is amongst the first in Africa that relates poliovirus laboratory containment in the context of the tOPV-bOPV switch in alignment with the Global Action Plan III. All identified infectious materials were destroyed and personnel trained to continue to destroy subsequent materials, a process that needs meticulous monitoring to mitigate the risk of poliovirus re-introduction to the population.